THE ROLE OF LPSK TOWARDS THE DISTRIBUTION OF LOSSES AND DISTRIBUTIVE JUSTICE TO VICTIMS - Widjaja, Gunawan; Wagiman; Widjaja, Liza (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
This article aims to analyze the role of the Witness and Victim Protection Agency (LPSK) in the distribution of losses experienced by victims and its contribution to realizing distributive justice. The problem formulations proposed in this research are: (1) What is the form of loss distribution provided by LPSK to victims of crime? and (2) What are the challenges faced by LPSK in implementing loss distribution and realizing distributive justice for victims? This research uses a normative juridical approach by analyzing the applicable laws and regulations as well as the LPSK annual report as research material.